The Rhomboid Flap for Facial Reconstruction Following Basal Cell Carcinoma Excision: A Case Report on Achieving Optimal Aesthetic and Functional Outcomes - Tilesky Caprizio Phoanda; Ferra Olivia Mawu; Oktavia Reymond Leomer Sondakh; Paulus Mario Christopher (HM Publisher, 2025)
Background: Reconstruction of the lower eyelid following oncologic surgery presents a formidable challenge due to the region's unique anatomy and functional importance. The primary goal is to restore the lamellar structure while avoiding ectropion, a complication with significant functional and aesthetic consequences. This report details the successful application of a rhomboid flap, a classic transposition flap, for a moderate-sized defect in this high-risk anatomical subunit. Case presentation: A 75-year-old male farmer presented with a 2x1 cm nodular basal cell carcinoma on his left lower eyelid. After surgical excision with 4 mm margins, a superolaterally based rhomboid flap was designed to close the defect. The procedure was performed under local anesthesia. The postoperative course was uncomplicated. Objective functional assessment at 12 weeks confirmed a normal lower lid position with margin-to-reflex distance 2 (MRD2) symmetrical to the contralateral eye and no evidence of ectropion or lagophthalmos. The cosmetic outcome was assessed as favorable using the Patient and Observer Scar Assessment Scale (POSAS), and the patient reported high satisfaction (5/5 on a Likert scale). Conclusion: This case report illustrates the successful use of a rhomboid flap for a moderate-sized lower eyelid defect, resulting in a favorable functional and aesthetic outcome without complications in the short-term follow-up period. The technique successfully restored tissue volume and preserved normal eyelid function, critically preventing ectropion. It supports the rhomboid flap as a robust and reliable option in the reconstructive surgeon's toolkit for this challenging anatomical area.